Structural investigation of samarium (SM) doped yttrium iron garnet (YIG) made by solid state reaction for dielectric resonator antenna applications - Hisyamuddin Hanif Ahmad, 1995-, author; Wan Fahmin Faiz Wan Ali, supervisor; Fakulti Kejuruteraan Mekanikal (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2018